Pengakuan Dan Perlindungan Hukum Hak Masyarakat Adat Atas Tanah Ulayat Dalam Upaya Pembaharuan Hukum Nasional - Hayatul Ismi (Jurnal Ilmu Hukum, 2012)
Land is  represent one of very elementary asset state of Indonesia because state and nation live and expand above land. Society of Indonesia position land at dimiciling very important, specially in society customary law. But, up to now not yet been made available by a complete information about unfolding and boundary of region included by various customary law of mentioned in this matter is customary right for land rights. This handing out conclude that rights of customary right for land in law of Indonesia confessed by through fundamental code of  agraria that is UU No. 5 year 1960. In this case the confession given by a state have the character of laminated and conditional because confession given to society of customary law and rights of its customary right for land.